Discussing development alternatives for the city of Madrid on the horizon Europe 2020: Challenges and threats from the perspective of knowledge workers - Simón Sánchez Moral (Anales de Geografía de la Universidad Complutense, 2013)
The Europe 2020 Strategy may show an alternative path to development that Madrid has followed in recent decades and whose contradictions and unbalances are revealed by the bursting of the financial-housing bubble and the economic crisis. From the reflexivity representing the approach of "smart specialization", in this paper we ask to what extent Madrid is ready to seize that opportunity taking into account the stock and characteristics of their workers in the knowledge economy. For this purpose, we use the Continuous Sample of Work Lives (MCVL) from the Social Security among other data sources that allows us to obtain an unusual image of the process of attracting "talent" to Madrid, as a strategic resource to achieve the "smart growth” promoted by the Strategy.